Nicholas L. Georgakopoulos, Principles and Methods of Law and Economics: Basic Tools for Normative Reasoning, Cambridge University Press - Camtridbe (etc.), 2005, 378 str., ISBN 978-0-521-53411: Recenzije knjig / Book review - Keresteš, Tomaž (LeXonomica, 2009)
Recenzija knjige / Book review
Keywords: book review; Nicholas L. Georgakopoulos, Principles and Methods of Law and Economics: Basic Tools for Normative Reasoning